2020
DOI: 10.1001/jamacardio.2019.4665
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Angiotensin-Neprilysin Inhibition After Acute Decompensated Heart Failure

Abstract: IMPORTANCE In PIONEER-HF, among stabilized patients with acute decompensated heart failure (ADHF), the in-hospital initiation of sacubitril/valsartan was well tolerated and led to improved outcomes compared with enalapril. However, there are limited data comparing the strategies of in-hospital vs postdischarge initiation of sacubitril/valsartan. OBJECTIVE To describe changes in N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels in patients recently hospitalized for ADHF and switching from taking enal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 16 publications
2
47
0
6
Order By: Relevance
“…Similarly, in human studies, the oxidative stress caused by chronic vascular disease (CVD) versus HFrEF cannot be differentiated. HF is more common in men [69][70][71]; however, the unequal gender distribution in our study may be due that women reach a similar HF risk as men only after the menopause [3]. In addition, we evaluated only the selected oxidative stress biomarkers, which is also a limitation of the study.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in human studies, the oxidative stress caused by chronic vascular disease (CVD) versus HFrEF cannot be differentiated. HF is more common in men [69][70][71]; however, the unequal gender distribution in our study may be due that women reach a similar HF risk as men only after the menopause [3]. In addition, we evaluated only the selected oxidative stress biomarkers, which is also a limitation of the study.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, the beneficial effects of these medical therapies were repeatedly associated with their potential to promote myocardial reverse remodeling manifested mainly by the reduction of left ventricular size and improvement of its function [ 18 ]. While paradigm-HF and pioneer-HF data clearly demonstrated superior clinical efficacy of ARNI therapy compared to ACEI in terms of reduced heart failure-associated hospital admissions, cardiovascular and all-cause mortality, until recently the association between these clinical effects and reverse remodeling of the failing myocardium remained unexplored [ 1 , 2 ]. Basing largely on the small patient cohorts and short-term follow-up recently published data support the association between ARNI and left ventricular reverse remodeling as these studies consistently showed an improvement in left ventricular ejection fraction (ΔLVEF +4–5%) and a decrease in left ventricular size (ΔLVEDD—6% or ΔLVEDV—8–10%) after three months of ARNI therapy [ 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that in HFrEF patient treatment with ARNI, compared to angiotensin converting enzyme inhibitor (ACEI) enalapril, resulted in significant benefits considering heart failure hospitalizations and cardiovascular (CV) and all-cause mortality [ 1 ]. Subsequent transition and pioneer-HF trials further demonstrated comparable safety and superior efficacy of ARNI over ACEI also in HFrEF patients with more advanced stages of the disease, largely establishing ARNI as an evolving first-line treatment approach in this patient population [ 2 , 3 ]. However, despite these encouraging findings, the underlying mechanisms still remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…DeVore et al [32] investigated this open-label extension treatment of sacubitril/valsartan and found similar levels of NT-proBNP between the enalapril and sacubitril/ valsartan groups after 4 weeks of ARNI treatment. However, the difference in the risk of cardiovascular death or rehospitalization for HF between the groups remained at 12 weeks following randomization (HR, 0.69; 95% CI, 0.49 to 0.97; p = 0.032) [32]. In another sub-study of the PIONEER-HF trial, soluble ST2 and high-sensitivity cardiac troponin T, which are considered surrogate markers of myocardial stress and injury, were significantly reduced in the sacubitril/valsartan group at the 1-and 4-week follow-up timepoints.…”
Section: Acute Heart Failurementioning
confidence: 97%
“…All participants in the PIONEER-HF trial completed 4 weeks of sacubitril/valsartan treatment following the 8-week study duration per protocol [31]. DeVore et al [32] investigated this open-label extension treatment of sacubitril/valsartan and found similar levels of NT-proBNP between the enalapril and sacubitril/ valsartan groups after 4 weeks of ARNI treatment. However, the difference in the risk of cardiovascular death or rehospitalization for HF between the groups remained at 12 weeks following randomization (HR, 0.69; 95% CI, 0.49 to 0.97; p = 0.032) [32].…”
Section: Acute Heart Failurementioning
confidence: 99%